Membangun Spirit Moderasi Beragama Melalui Seni Karungut di Desa Tewang Darayu - A. Gede Wiranata; Muslimah Muslimah; Isabella Jeniva; Sopariyah Sopariyah; M. Khoirul Ikhsan; Angel Keristina; Maha Dewi Rambu Dewata; Rindi Juniari. S; Joana Joana; Wilda Cahyani; M. Nur Afandi; Anggun Anggun; Nopia Santika; Nanda Anjelia; Yoga Yoga (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
The art of Karungut and traditional Dayak music, rich in values of togetherness, tolerance, and cultural wealth, has the potential to be an effective tool for instilling the spirit of religious moderation in the younger generation. This project focuses on integrating Karungut art as a medium for education and character building that is moderate, tolerant, and respectful of diversity. The main goal of this initiative is to increase the awareness and understanding of the youth in Tewang Darayu Village about the importance of religious moderation through Karungut art. Additionally, the program aims to preserve traditional Dayak art so it can continue to be passed down to future generations. The method used in this project is Participatory Action Research (PAR), which emphasizes the active participation of all community members. The first step involves socialization and Focus Group Discussions (FGD) with village officials, religious leaders, traditional leaders (Pisur), and the general public to identify their needs and expectations for this program. This project has achieved several positive outcomes. First, there has been a significant increase in the understanding and awareness of the younger generation regarding the importance of religious moderation. Second, Karungut art and traditional Dayak music have regained a place in the hearts of the community, especially among the younger generation. Third, this program has also strengthened social bonds in Tewang Darayu Village, as it involved the active participation of various community members, from village officials and religious leaders to traditional leaders and the general public. Thus, this program has not only succeeded in preserving Karungut art but also in building a more moderate and tolerant community.